1999
DOI: 10.1002/(sici)1521-3935(19990701)200:7<1644::aid-macp1644>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation and antitumour activity of platinum(II) complexes of novel functionalised poly(amido amine)s

Abstract: SUMMARY: Polyamidoamine polymers were prepared by hydrogen-transfer polyaddition of 2-methylpiperazine to 2,29-bis(acrylamido)acetic acid sodium salt to yield PAA-1, polyaddition of amino-b-cyclodextrin and 2-methylpiperazine to 2,29-bis(acrylamido)acetic acid to give PAA-2 and polyaddition of the same amino-bcyclodextrin and 2-methylpiperazine to 1,4-bis(acryloyl)piperazine to produce PAA-3. These polymers were reacted with cisplatin to give products containing between 8 -70 wt.-% platinum. The amount of plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 15 publications
2
32
0
1
Order By: Relevance
“…24 The ultimate cytotoxic actions of many types of these conjugates are met when they are used in vivo as an example the polymer-drug conjugates are very stable and not able to release the specified drug when they are inside the tumor cell environment for their final action. 25 In this study we have shown the synergistic toxic effect of the anionic linear-globular dendrimers (with terminal citric acid groups) conjugated to the surface of cisplatin.…”
Section: Discussionsupporting
confidence: 72%
“…24 The ultimate cytotoxic actions of many types of these conjugates are met when they are used in vivo as an example the polymer-drug conjugates are very stable and not able to release the specified drug when they are inside the tumor cell environment for their final action. 25 In this study we have shown the synergistic toxic effect of the anionic linear-globular dendrimers (with terminal citric acid groups) conjugated to the surface of cisplatin.…”
Section: Discussionsupporting
confidence: 72%
“…2-Methylpiperazine (2-MePip) was also obtained from Fluka but was recrystallised from hexane, its purity was determined titrimetrically before use. 2,2-Bis(acrylamido)acetic acid (BAC) and bisacryloylpiperazine (PB) were synthesised as previously described, [18,19] and their purity was determined titrimetrically (BAC) or by NMR (BP) just before use.…”
Section: Methodsmentioning
confidence: 99%
“…administration in mice, with different grades of toxicity and activity, although none of them were active against the primary tumour [49]. More recently, PAAs have been adopted as carriers for anticancer drugs such as mytomycin C [50], platinates [51] and doxorubicin. Conjugation of doxorubicin to polymers improves drug solubility, increases its blood half-life, decreases its toxicity, and mediates more efficient tumour targeting [52].…”
Section: Paa Applications In Drug Deliverymentioning
confidence: 99%
“…It is a rather weak polymeric base with, on average, 0.55 positive charges per unit at pH 7.4. All these polymers had been reported as vectors for the intracellular delivery of nucleic acids [56,61,71], whereas ISA1 and ISA23 had been also studied for protein delivery [45,62,71] and as anticancer drug carriers [51,53]. ISA23 in particular has been proven to be endowed with stealth-like properties without selectively concentrating in the liver [44], while a significant portion of AGMA1 did show hepatic localization after intravenous injection in mice [42].…”
Section: Paas For the Targeted Delivery Of Antimalarial Drugsmentioning
confidence: 99%